ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል አንድ - International Livestock Research Institute (International Livestock Research Institute, 2022)
‘Gebeta ’, the Amharic word for plate or dish, is the title of a weekly radio program series focusing on livestock feed and forage innovations in Ethiopia. In episode one, which aired on Debre Birhan Fana FM 94.0 on 28 June 2022, Getnet Assefa, a consultant at ILRI discusses the contribution of the livestock sector to the national economy and its significance in the livelihoods of Ethiopian farmers. This radio program series is produced by Africa RISING and AICCRA as part of the partnership – Use of Interactive radio to scale-up feed and forage innovation technologies in Ethiopia.